Effect in virulence of switching conserved homologous capsular polysaccharide genes from Klebsiella pneumoniae serotype K1 into K20. Issue 5 (4th July 2017) - Lin, Chii-Lan; Chen, Fei-Hsu; Huang, Li-Yueh; Chang, Jen-Chang; Chen, Jiun-Han; Tsai, Yu-Kuo; Chang, Feng-Yee; Lin, Jung-Chung; Siu, L. Kristopher
ABSTRACT: The capsular polysaccharides in different serotypes of Klebsiella pneumoniae (KP) coded by the (CPS) gene cluster are characterized by a conserved and a hyper-variable region. We performed a virulence study by switching genes in the highly conserved region of the CPS cluster between strains. Six genes in the CPS conserved region in serotype K20, including galF, acidPPc, wzi, wza, wzb and wzc, were knocked out and replaced by the homologous genes from serotype K1. Compared to the parental K20 strain, the mutants showed a decline in lethality (LD50 ) in mice from 10-fold to > 10 5 -fold and were categorized in terms of the effect on virulence as low (L) for galF and acidPPC, moderate (M) for wzi, and high (H) for wza, wzb and wzc . Although substituting the acidPPC gene from K1 for acidPPC in the K20 strain fully restored virulence, substitution with the wzi, wza, wzb or wzc homologs from K1 did not. The restoration with wzi from K1 led to a partial restoration of virulence, with the LD50 in mice changing from 10 4 to 10 3 CFU. For the wza, wzb and wzc genes, Complementation of K20 wza, wzb and wzc from K1 resulted in varied degrees of lethality in mice. Variable improvement in serum killing and phagocytosis was observed when the knockout mutants were compared with the gene-switched strains. In conclusion, homologous genes for capsule synthesis failed to exhibit the same functionality when switched between serotypes and virulence was decreased in different degree in according to the genes' homology.